Compliance with Mining Reclamation Policies in the Atiwa District - Obeng-Koranteng, E. (University of Ghana, 2020)
Environmental governance in the extractive industry has seen many reforms especially due to the activities of both illegal and legal small-scale miners. There is no doubt that mining contributes significantly to the nation’s economy though the process has adverse impacts that need to be addressed. Reclaiming abandoned mine pits is one way of mitigating the impact of mining. In spite of this, the level of compliance implementation has not been evaluated. The study sought to assess compliance with mining reclamation policies in the Atiwa District, specifically, to review mining regulations; evaluate the role of stakeholders and the level of compliance; examine the extent of landscape degradation and ascertain community perception of reclamation in the District. A total number of 387 questionnaires were administered to generate the requisite primary data. Remotely sensed data were also used to determine the extent of environmental damage. Context analysis was used to analyze data for the review of regulations and the role of stakeholders and chi-square tests for community perception. A major observation was the wanton environmental destruction by mining activities resulting in abandoned open pits, pollution of the Birim River and the destruction of the vegetation. This was the result of unspecific reclamation regulations and technical language used in policy formulation. The study further revealed a generally low level of compliance of stakeholders to mining regulations. Some weaknesses that emerged include challenges in enforcement and allegations of bribery and corruption. The study concluded that with pragmatic policy formulation and the engagement of all stakeholders, there would be a win-win situation to ensure sustainable development. Suggested recommendations include formulating specific mining reclamation policies that are transparent; collaborating to undertake extensive research on reclamation; legally recognizing the Tributer system and sensitization of affected communities on their rights regarding the granting of social licenses.
MPhil. Environmental Science
Keywords: Mining; Mining Reclamation Policies; Atiwa District; Ghana; Environmental; Pollution